Przywiązanie w dzieciństwie w aspekcie wybranych sytuacji trudnych dzieci - Cywińska , Małgorzata (Studia Edukacyjne, 2023)
The family plays a crucial role in shaping an individual’s personality and influencing emotional, social, and cognitive development. J. Bowlby underscores the significance of early attachments, particularly with the mother, in the proper formation of an individual. The primary and biologically rooted need for proximity to the caregiver profoundly impacts a child’s well-being. This study explores the repercussions of challenging childhood experiences, including maternal abandonment or frequent distancing, on the individual’s functioning not only in childhood, but also throughout adolescence and adulthood. The behavior of attachment figures, especially the caregiver acting as the mother, determines the quality of the child’s attachment, classified as either trusting, anxiety-avoidant, anxiety-ambivalent, or disorganized. Insecure attachments, specifically anxiety-avoidant and anxiety-ambivalent bonds, along with disorganized attachment, can give rise to various difficult situations for individuals. The focus, particularly on disorganized attachment, highlights the heightened risk of mental disorders, behavioral issues, and personality disorders. This article delves into John Bowlby’s attachment theory, elucidating its key aspects, and draws connections to difficult situations experienced by preschool and early elementary school children with diverse attachment types. These situations encompass conflicts, loneliness, peer rejection, and failures.